(untitled) (Asian Journal of Applied Sciences, 2017)
This manuscript describes the possibility of permanent magnet synchronous generator (PMSG) based wind energy generation using variable frequency transformer (VFT)with an optimized particle swarm optimization based PID (PSO-PID) controller for reducing power fluctuations. VFT is a recent power transmission technique used to eliminate the power electronics needed in the conventional wind energy conversion system. To analyze the performance of the proposed method the MATLAB-Simulink model has been developed and tested under various loading condition. The efficiency of the proposed method has been verified by comparing the total harmonic distortion (THD) of the output voltage, current, and efficiency of the proposed method with the conventional method. The simulation results indicate that the proposed PSO-PID method does not produce harmonics and easy to implement. The cost analysis has been carried out and it shows that the proposed method is cheaper than the conventional method of generating wind power.